Comparison of the microbiological and hygienic quality of turkey meat between six districts of the Kenitra city - Jaber Hassna (EDP Sciences, 2021)
Meat is known to be one of the vehicles for many diseases to humans. The aim of this study is the comparison of the microbiological and hygienic quality of fresh turkey meat marketed in the most popular districts of Kenitra city. Fresh meat samples were taken from stores localized in six different districts. Microorganisms tests were conducted according to the appropriate standards. The Aerobic Mesophilic Flora (AFM) was most counted in district five (7.69±0.212 log10ufc/g), while the highest total and fecal coliform charges were obtained in district six with rates of 7.68±0.160 and 6.89±0.132 log10ufc/g, respectively. Cases of Salmonella spp were observed in all districts, except district five with frequencies up to 10.71%. Pseudomonas aeuroginosa charge was high in district five and its prevalence was high (21.42%) in districts two, four and six. Regarding Clostridium perfringens, the charges were up to 2.11±0.55 log10ufc/g in district six and a high prevalence of 42.85% was in district four. Escherichia coli showed dominance in all the districts studied with a high prevalence in district four with a rate of 75% and a high charge in district five (4.37 log10ufc/g). The presence of Staphylococcus aureus was significant in district four with a rate of 28.57% and a high concentration in district five (4.47 log10ufc/g). This study has shown great variability in the results found between the different districts and the rate of contaminations affecting this product. In fact, this microbiological and hygienic quality of raw turkey meat sold in these districts was judged marginal indicating the need for improved hygienic standards.